Prototipe Troli Pengikut Otomatis Menggunakan Pengolahan Citra Kamera Pixy Cmucam 5 Berbasis Arduino - Pradipta, Ramadhan Singgih; , Ir. Pratomo Budi Santosa, MT (2016)
Trolleys are widely used in modern markets. As a porter frequent use of the trolley is not returned after use or hinder the other trolley. With the advance of the current era do a combination of technology with a trolley in order to facilitate the activity of man in the shop and tackle the problem in the shop. One of them is to create a prototype automated trolleys followers. Prototyping aims to study early 4 wheeled robot models that will be developed into a much larger scale. The prototype system automatically follow an object moving trolley in front of him. Using the camera sensor pixy CMUcam 5 as detection of objects with the color orange. The colors on the simulated object with rectangular board with the color circle diameter of 10 cm. Image processing such as the introduction of color into four basic movements of a DC motor. The robot moves follow an object in real time by tracking color techniques. Arduino Uno as control of the entire system and SRF05 ultrasonic sensors located in the front and rear as distance keeper trolley prototype. The test results showed a prototype trolleys do the tracking of objects based space coordinates x 0-320 point of view, divided 4 parts. The coordinates of x 0-80 robot rotates to the left, the point coordinates x 80-160 robot turn left, the coordinate of the center robot forward, the coordinates of 160-240 robot to turn right, and coordinate points 240-320 robot rotates to right. Distance to detect objects only up to a distance of 600 cm with a travel time of 15.36 seconds, at a distance of 650 cm pixy camera CMUCam 5 is not mapu detect objects. Robot backwards when the object in front of the robot enters a distance of approximately 15 cm. And the robot forward as the obstruction behind the robot is less than 15 cm to the ultrasonic sensor.